FACTORS AFFECTING MSME’s INTEREST TO APPLY FOR BUSINESS FINANCING IN ISLAMIC FINANCIAL INSTITUTIONS - Rohmah, Mayda Miftakhur; Rintasari, Nugraheni (Muhammadiyah University Press, 2018)
This study aims to determine the effect of services, procedure, reputation, and promotion on the MSMEs? interest to apply for business financing provided by Islamic financial institutions. It is a quantitative research. The data were primary data obtained from questionnaires that were distributed directly to the respondents. As many as 58 MSME actors in the Manding Leather Craft Center, Bantul, Indonesia, were involved as the respondents. The sampling technique was purposive sampling as a type of the non probability sampling method. Data analysis methods included multiple linear regression, classical assumption test, and hypothesis testing (t-test and F-test). Data processing required the assistance of SPSS 17.0. The results of the t-test show that each independent variable partially affects the MSMEs? interest to apply for Islamic financing. Furthermore, the results of the F-test indicate that the variables of services, procedure, reputation, and promotion simultaneously affect the MSMEs?interest to apply for business financing provided by Islamic financial institutions.